2020
DOI: 10.3390/genes11050481
|View full text |Cite
|
Sign up to set email alerts
|

ATP2A2 SINE Insertion in an Irish Terrier with Darier Disease and Associated Infundibular Cyst Formation

Abstract: A 4-month-old female Irish Terrier presented with a well demarcated ulcerative and crusting lesion in the right ear canal. Histological analysis revealed epidermal hyperplasia with severe acantholysis affecting all suprabasal layers of the epidermis, which prompted a presumptive diagnosis of canine Darier disease. The lesion was successfully treated by repeated laser ablation of the affected epidermis. Over the course of three years, the dog additionally developed three dermal nodules of up to 4 cm in diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The clinical and histopathological findings in the studied Shih Tzu largely resembled previous descriptions of confirmed or suspected Darier disease in dogs (Linek et al, 2020; Müller et al, 2006; Olivry & Linder, 2009; Sueki et al, 1997). In humans, Darier disease is characterized by waxing‐and‐waning development of warty papules and plaques in seborrheic areas (central trunk, flexures, scalp, and forehead) associated with distinctive nail abnormalities.…”
Section: Figuresupporting
confidence: 85%
See 2 more Smart Citations
“…The clinical and histopathological findings in the studied Shih Tzu largely resembled previous descriptions of confirmed or suspected Darier disease in dogs (Linek et al, 2020; Müller et al, 2006; Olivry & Linder, 2009; Sueki et al, 1997). In humans, Darier disease is characterized by waxing‐and‐waning development of warty papules and plaques in seborrheic areas (central trunk, flexures, scalp, and forehead) associated with distinctive nail abnormalities.…”
Section: Figuresupporting
confidence: 85%
“…This calcium pump plays a key role in intracellular calcium signaling which in turn is central to the regulation of cell‐to‐cell adhesion, differentiation, and cornification in the epidermis (Foggia & Hovnanian, 2004). A canine form of Darier disease has been reported in an Irish Terrier with a heterozygous intronic SINE insertion in ATP2A2 that resulted in a near‐complete loss of functional transcripts from the mutant allele (OMIA 002265‐9615; Linek et al, 2020).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Dogs have a sizeable population of active long interspersed nuclear element (LINE)-1 insertions (52). Both short interspersed nucleotide element (SINE) and LINE-1 insertions are a common cause of inherited diseases in dogs (75)(76)(77)(78)(79)(80)(81)(82)(83)(84). Retrogene insertions represent one particular class of structural sequence variation that has occurred several times in dogs (85) and that may be relevant for diseases, for example, as in chondrodysplasia and chondrodystrophy (25,26).…”
Section: Variant Categoriesmentioning
confidence: 99%
“…Several mutations in different genes have been associated with this disease, including mutations in the genes encoding keratin 2 and 9, and desmoglein 1 [132], and a variant is the missense c.155G > C in the FAM83G gene, which encodes a protein that has a largely unknown function [133]. In this same breed, the heterozygous SINE insertion into the ATP2A2 gene is associated with Darier canine disease, a rare form of genodermatosis that affects different breeds [134,135]. Concretely, Linek et al (2020) showed a demarcated ulcerative and crusting lesion in the ear canal in one Irish Terrier, related to canine Darier disease [135].…”
Section: Other Genodermatosismentioning
confidence: 99%